Laparoscopic surgery for colorectal cancer in a patient with intestinal malrotation: a case report - Yadav, Dipesh Kumar; Li, Min; Xu, Jiahao; Lin, Sisi; Bao, Dandan; Huang, Hanzhang; Yang, Zhangwei; Hu, Yiren (Frontiers in Oncology, 2025)
Intestinal malrotation (IM), a rare congenital anomaly, poses significant surgical challenges when coexisting with colorectal cancer—an association reported in fewer than 60 cases globally, predominantly in Japan. This study presents the first documented case in China of ascending colon cancer with nonrotation IM, successfully managed via laparoscopic right hemicolectomy with D2 lymphadenectomy. A 79-year-old female presented with abdominal pain, weight loss, and melena. Colonoscopy revealed an ascending colon mass, confirmed as adenocarcinoma. Preoperative contrast-enhanced CT demonstrated left-sided colonic malposition, an “M”-shaped colon, and anomalous ileocolic vasculature originating from the left of the superior mesenteric artery. A multidisciplinary team employed meticulous preoperative planning, utilizing multiplanar CT reconstruction to navigate anatomical complexity. Laparoscopic surgery involved adhesiolysis, division of Ladd’s bands, and D2 dissection, achieving R0 resection (pT3N0M0) with 50 mL blood loss and no intraoperative complications. The patient recovered uneventfully, discharged on postoperative day 9, with no recurrence at 18-month follow-up. This case underscores the feasibility of minimally invasive techniques in IM-associated malignancies when guided by embryological insight and advanced imaging. Key technical strategies included adaptive port placement, stepwise anatomical correction, and vascular tracing to ensure oncological adequacy. The successful integration of laparoscopic principles with anomaly-specific modifications highlights a paradigm for managing such rare presentations. Our findings emphasize that IM’s anatomical complexities need not preclude laparoscopic benefits, advocating for global case-sharing to refine standardized protocols and expand minimally invasive options in complex surgical oncology.